Colloidal dual-band gap cell for photocatalytic hydrogen generation. Issue 40 (29th September 2015) - Li, Wei; O'Dowd, Graeme; Whittles, Thomas J.; Hesp, David; Gründer, Yvonne; Dhanak, Vinod R.; Jäckel, Frank
Abstract : Quantum efficiencies (QE) for H2 generation in spherical, Pt-decorated CdS nanocrystals can be tuned by quantum confinement, resulting in higher QE for smaller crystals. This enables a colloidal dual-band gap cell using differently sized crystals and optimising overall H2 generation. Abstract : We report that the internal quantum efficiency for hydrogen generation in spherical, Pt-decorated CdS nanocrystals can be tuned by quantum confinement, resulting in higher efficiencies for smaller than for larger nanocrystals (17.3% for 2.8 nm and 11.4% for 4.6 nm diameter nanocrystals). We attribute this to a larger driving force for electron and hole transfer in the smaller nanocrystals. The larger internal quantum efficiency in smaller nanocrystals enables a novel colloidal dual-band gap cell utilising differently sized nanocrystals and showing larger external quantum efficiencies than cells with only one size of nanocrystals (9.4% for 2.8 nm particles only and 14.7% for 2.8 nm and 4.6 nm nanocrystals). This represents a proof-of-principle for future colloidal tandem cell.